STRATEGI PEMERINTAH DESA DALAM MENGELOLA SAWAH TKD (TANAH KAS DESA) DI DESA SELING KECAMATAN TABIR KABUPATEN MERANGIN - Miranti Miranti; Siti Maryam; Mila Adrianis (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Village treasury land is a village asset with great potential, good and appropriate management is a step that must be implemented considering that village treasury land is a large asset for village income compared to other village assets. From the description above, Seling Village, Tabir District, has a large area of ​​village land which should get maximum results, but in reality the income from this village land is not optimal. The aim of this research is to find out the village government's strategy in managing TKD (Village Cash Land) rice fields in Seling Village, Tabir District, Merangin Regency, and to find out the obstacles faced by the village government in managing TKD (Village Cash Land) rice fields in Seling Village, Tabir District, Merangin Regency. The method used in this research is a qualitative research method which is a descriptive study. The method used in this research is a qualitative research method which is a descriptive study. The informant selection technique used by researchers in this research was the purposive sampling method (a technique for determining samples with certain considerations). The results of this research show that the village government's strategy in managing TKD rice fields (Village Cash Land) in Seling Village, Tabir District, Merangin Regency is: Optimizing income, optimizing land use, and submitting irrigation improvements to the Regional Government. The obstacles faced by the village government in managing TKD rice fields (Village Cash Land) in Seling Village, Tabir District, Merangin Regency are: The lack of agricultural infrastructure and the lack of formation of BUMDes.